Tinta e perspectiva: o exílio e a representação da mulher na obra de Remedios Varo (1940-1963) - Plassmann, Giulia Beatriz Schossler (2024)
Remedios Varo is a Spanish artist who during her life experienced countless trips, both due to her father's profession and due to the imminent wars, in particular, the Spanish Civil War and the Second World War. The artist had a unique style of painting that portrays resolutions of personal problems, pain, conflicts, bonds and feelings, which consciously or not went beyond himself and his subjectivity, reaching common experiences, criticizing society and the time in which he lived. The core of this work will be to investigate: 1) the artist's representations as metaphors about exile and its consequences; 2) the artist’s female representations; 3) the artist's representations of scientific advances and their uses and consequences in the inter-war period. Concluding that Remedios Varo was an intellectual artist of her time who, through her works, exposed her questions and indignations with some themes and issues that bothered her in the midst of her experiences, reaching questions about society, culture, exile, women, wars and scientific advances.